Psychological distress and obesogenic behaviour among a nationally representative sample of in-school adolescents in anguilla - Karl Peltzer (2022)
This investigation aimed to report the prevalence and its correlates of obesogenic behaviour among adolescents in Anguilla. Cross-sectional nationally representative data were analysed from 813 adolescents (15 years median age) that participated in the “2016 Anguilla Global School-Based Student Health Survey (GSHS).” Obesogenic behaviour included 80.7% physical inactivity, 59.4% sedentary behaviour, 82.1% inadequate fruit and vegetable intake (<5 servings/day), 52.3% daily soft drink consumption and 42.5% fast food consumption (≥3 days/week). The total obesogenic behaviours were 0 = 0.5%, 1 = 5.7%, 2 = 21.9%, 3 = 31.4%, 4 = 27.5% and 5 = 13.0% (81.5% 3-5 obesogenic behaviours), with a total mean of 3.19 (SD = 1.1). In adjusted linear regression analysis, medium parental support (Adjusted Exp (Coef.)-AEC: 0.79, 95% Confidence Interval-CI: 0.64-0.98) and school attendance (AEC: 0.71, 95% CI: 0.60-0.84) were negatively associated with obesogenic behaviour. In addition, in univariate analysis, female sex was negatively and multiple psychological distress was positively associated with obesogenic behaviour. High obesogenic behaviour was observed and several associated variables were identified which can aid in designing intervention strategies.